The use and trust of information sources related to the efficacy and safety of dietary supplements among US vs Chinese consumers: an exploratory study - Andrew M. Forman; Ven Sriram (Journal of the Academy of Business and Emerging Markets)
Dietary supplements are generally exempt from strict governmental regulations, leaving consumers to rely on various information sources to judge the safety and efficacy of these products. Given the differences in the US and Chinese marketplaces concerning government regulation and business responsibility, this study addresses the roles of different information sources for US and Chinese consumers. Findings reveal that while consumers in both countries rank family/friends and health professionals high (and marketer sources low), US consumers are more apt to trust online sources. While neither American nor Chinese consumers trust regulators to ensure supplement safety, Chinese consumers have lower trust than Americans.